Fecal microbiota transplantation for Clostridium difficile infection in Taiwan: Establishment and implementation - Tien-Ching Lin (Journal of Microbiology, Immunology and Infection, 2019)
Clostridium difficile infection (CDI) remains a major public health issue, and fecal microbiota transplantation (FMT) has become one of the standard therapies for recurrent or refractory CDI. When compared to medical therapies, such as metronidazole or vancomycin, FMT has a high rate of treatment response with acceptable safety and efficiency. Following promulgation of the amendments in September 2018 in Taiwan, FMT has been indicated for recurrent or refractory CDI. The Taiwan Microbiota Consortium contributed to the Taiwan FMT Expert Consensus, which established basic norms and stipulated essential principles, including the indications for transplantation, eligible locations and personnel, donor screening policies, fecal sample handling, and post-FMT follow-up. However, establishing an eligible FMT team in a qualified hospital remains a clinical challenge, and the requirement for facilities and well-screened donors impedes the implementation of FMT. In this review, we aim to provide domestic FMT teams with explicit instructions to facilitate realization and increase the practice of FMT. Based on the Taiwan FMT Expert Consensus and current regulations, we performed a literature review and integrated the experiences of Taiwanese multidisciplinary experts into this article. The content intends to offer clinicians up-to-date evidence and highlight the essential points of FMT. Keywords: Clostridium difficile infection, Fecal microbiota transplantation, Gut dysbiosis